Resisting National Sentiment: Friction between Irish and English Jesuits in the Old Society - McCoog, Thomas M. (Journal of Jesuit studies, 2019)
Pedro de Ribadeneyra, first official biographer of Ignatius of Loyola, showered praise upon him and his companions for abandoning immoderate sentiment "for particular lands or places" in their quest for "the glory of God and the salvation of their neighbors." Superior General Goswin Nickel praised a Society conceived in Spain, born in France, approved in Italy, and propagated in Germany and elsewhere. Out of diversity Ignatius had forged unity. Ribadeneyra prayed that nothing would ever threaten this union. His prayers were not heard: the Society's internal unity was often endangered by national sentiment despite congregational attempts to curtail and eliminate it. This article does not purport to be an exhaustive study of localism versus internationalism—although such a study is needed—but an investigation of relations between Irish and English Jesuits principally in the seventeenth century. Individual Jesuits did in fact cooperate, but there were limits. A proposal in 1652 that the independent Irish mission become part of the English mission was that limit.